Perancangan Antar Muka Wearable Sistem Bagi Atlet - Ni Wayan Sani Utari Dewi; Cokorda Pramartha (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Technological developments have had a huge impact on various areas of life, including the world of sports. Today, athletes are leveraging various technologies to improve their performance and gain a better competitive advantage. Athletes must comply with the rules of the game and comply with the rules and regulations that apply to their game. hours of sleep is one of the most important factors in maintaining the stamina of athletes, according to the coach's directions. This study aims to make it easier for coaches to monitor the sleep hours of athletes being mentored. In order to improve the athlete's heart rate monitoring, an application was formed in the form of a prototype. The method used in this study is the mid-fidelity prototype which is the development of a prototype design model. Mid-fidelity prototype is a method for initial design, for purposes after detailed design and usability validation.